Relationship between levator ani and bony pelvis morphology and clinical grade of prolapse in women. Issue 6 (10th April 2015) - LI, Ran; Song, Yanfeng; Ma, Ming
<x xml:space="preserve">Abstract</x> The aim of this study was to assess the morphological features of the levator ani and bony pelvis in women with different grades of prolapse. Ninety Chinese women with different grades of uterine prolapse were studied, 18 in each stage of prolapse from I to IV, and 18 asymptomatic nulliparous volunteers as normal controls. Three‐dimensional (3D) models that included the pelvic bones, levator ani, pubic symphysis, sacrum, and coccyx were generated from magnetic resonance (MR) images. The width and length of the levator hiatus and levator symphysis gap, the width of the iliococcygeus, and the iliococcygeal angle were measured to quantify levator ani morphology; the intertuberous diameter, interspinous diameter, subpubic angle, and pubococcygeal line were measured to characterize the morphology of the bony pelvis. Four patterns of levator ani morphology among women with and without prolapse were distinguished. Among the bony pelvis parameters, no measurement differed significantly between the subjects with prolapse and normal controls, or among subjects with different grades of prolapse. There were significant differences in the width and length of the levator hiatus and levator symphysis gap between women with prolapse and normal controls. Our pilot data help to elucidate bony pelvis and levator ani morphology in women with and without pelvic organ prolapse. In contrast to the iliococcygeus muscle, changes in the morphological features of the pubovisceral muscle are more likely to accompany prolapse. Clin. Anat. 28:813–819, 2015. © 2015 Wiley Periodicals, Inc.